Efeito da depleção de nitrogênio no crescimento, morfologia e composição bioquímica de Picocystis salinarum Lewin como matéria-prima para a produção de biodiesel - Delgado, Ronald Mauricio Tarazona (2019)
In recent years, biodiesel production has attracted worldwide attention due to the awareness of the depletion of fossil fuels, and microalgae biomass is considered a promising raw material. To optimize the biodiesel production process from this resource, the selection of the strain and identification of its cultivation conditions to maximize lipid productivity and improving the fatty acid profile are necessary. The present study aims to analyze the effect of three concentrations of nitrogen depletion (0.5, 0.25 e 0.125 N) on the growth, morphology and biochemical composition of native microalgae Picocystis salinarum Lewin in two culture media (f/2 and J/1) as a potential source of raw material for biodiesel. Cultures were carried out in erlenmeyers, in triplicate and under controlled physicochemical conditions. Analysis of cell density, growth kinetics, dry mass, photosynthetic pigments, transmission electron microscopy (TEM) and determination of protein, carbohydrate, lipid and fatty acid methyl ester (FAME) contents were performed. The cell density and dry mass of P. salinarum decreased proportionally with nitrogen depletion in the f/2 medium, with the maximum values of 13,1 x 106cel.mL-1 and 0,89 g.mL-1 were registered in the control (1 N). In the J/1 medium, depletion didn’t influence growth measures, registered values of 19,7 ± 1,1 x 106cel.mL-1 and 0,96 g.mL-1 . Nitrogen depletion promoted the formation of lipid bodies and starch grains as reserve organelles evidenced by TEM. In the treatment of 0.125 N of the f/2 medium, the lipid bodies appeared markedly, whereas in the J/1 medium the presence of lipid bodies and starch grains occurred together. The content of pigments was also influenced by nitrogen depletion, in f/2 medium there was reduction of chlorophyll a and b (0,24 and 0,14 µg.mL-1 ) and increased carotenoids (3,35 µg.mL-1 ) in relation inversely proportional to the concentration of nitrogen tested. Depletion in the J/1 medium didn’t cause significant difference in the pigments relative to the control. In the f/2 medium, protein (2,9%) and carbohydrate (31%) content decreased with nitrogen depletion, lipid content (33,8%) was elevated, becoming the most predominant biomolecule (0.125 N). Nitrogen depletion in the J/1 medium stimulated the lipid content (22.3%) and carbohydrates (32%). In the 0.5 N treatment, in both culture media, saturated fatty acids (SFA) were the most representative of FAME, mainly due to the increase of palmitic acid. By the high concentration of SFA in the 0.5 N treatments in both culture media (996,08 µg.g-1ms in f/2 medium and 959,09 µg.g-1ms in J/1 medium) and low level of polyunsaturated fatty acids (PUFA) (19,87 µg.g-1ms in f/2 medium and 0,37 µg.g-1ms in J/1 medium), the biomass of P. salinarum proved to be ideal for use in industry as a source of raw material for the production of biodiesel.